Parallel Double Snakes. Application to the segmentation of retinal layers in 2D-OCT for pathological subjects. Issue 12 (December 2015) - Rossant, Florence; Bloch, Isabelle; Ghorbel, Itebeddine; Paques, Michel
Abstract: In order to segment elongated structures, we propose a new approach for integrating an approximate parallelism constraint in deformable models. The proposed Parallel Double Snakes evolve simultaneously two contours, in order to minimize an energy functional which attracts these contours towards high image gradients and enforces the approximate parallelism between them by controlling their distance to a centerline under regularity constraints of this line. The proposed approach is applied on retina images, for segmenting retinal layers in optical coherence tomography images of pathological subjects (and it applies to healthy subjects as well). Results are evaluated by comparing with manual segmentations for three retinal layers, and provide a similarity index above 0.87, sensitivity between 0.85 and 0.93, and specificity between 0.84 and 0.94. These results are within the range of intra and inter-expert variability. Moreover, quantitative studies demonstrate that, in our application, our Parallel Double Snake (PDS) model outperforms other parametric active contour algorithms integrating parallelism information. Abstract : Highlights: Original segmentation method for elongated structures. Integration of an approximate parallelism constraint in deformable models. Application to retina imaging (retinal layers in OCT for pathological subjects). Results are accurate and within the range of intra and inter-expert variability.